Diaphragmatic movement in hemiplegic patients measured by ultrasonography. Issue 9 (September 1994) - Cohen, E; Mier, A; Heywood, P; Murphy, K; Boultbee, J; Guz, A
Abstract : BACKGROUND–It is known that automatic breathing is controlled by centres in the lower brain stem, whereas volitional breathing is controlled by the cerebral cortical centres. In hemiplegia, lesions above the brain stem result in paralysis of limb muscles. This study was performed to determine whether the diaphragm might also be affected in patients with hemiplegia. METHODS–Studies were performed in six normal control subjects and in eight patients with complete hemiplegia caused by a lesion above the brain stem, all with no known chest disease. Full lung function tests were performed. Diaphragmatic excursion and inspired volume (VT) were measured simultaneously by M mode ultrasonography and respiratory airflow measurements. Recordings of diaphragmatic excursion were performed on each side separately during volitional and automatic breathing at a similar range of VT. RESULTS–Lung function tests lay within the normal range in all the control subjects. In the hemiplegic patients mean (SD) vital capacity was 79 (18)% and residual volume was 123(30)% of predicted. Total lung capacity and functional residual capacity were in the normal range. In the control subjects no significant difference in diaphragmatic excursion was found between volitional and automatic breathing for the same range of inspired volume. By contrast, there was a significant decrease in diaphragmatic excursion during volitional breathing compared with automatic breathing on the affected side in four of the eight hemiplegic patients. CONCLUSIONS–In four of eight hemiplegic patients reduced diaphragmatic movement was present on the paralysed side during volitional inspiration when compared with automatic inspiration. The hemidiaphragm may be involved on the affected side in patients with hemiplegia.